2024
DOI: 10.1162/nol_a_00116
|View full text |Cite
|
Sign up to set email alerts
|

Lexical-Semantic Content, Not Syntactic Structure, Is the Main Contributor to ANN-Brain Similarity of fMRI Responses in the Language Network

Abstract: Representations from artificial neural network (ANN) language models have been shown to predict human brain activity in the language network. To understand what aspects of linguistic stimuli contribute to ANN-to-brain similarity, we used an fMRI dataset of responses to n = 627 naturalistic English sentences (Pereira et al., 2018) and systematically manipulated the stimuli for which ANN representations were extracted. In particular, we i) perturbed sentences’ word order, ii) removed different subsets of words, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 103 publications
(213 reference statements)
0
2
0
Order By: Relevance
“…Some recent work has begun to attempt isolating the aspects of model representations that affect model-to-brain alignment. For example, Kauf et al (2024) performed a series of experiments where model representations were obtained for different perturbations of a linguistic stimulus (e.g., scrambling the word order or dropping/replacing some of the words) and then related to neural representations of an intact stimulus in order to see which perturbations affect model representations negatively. They found that word-level and compositional semantic information appears to be more important than information related to the syntactic structure in the model-to-brain alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent work has begun to attempt isolating the aspects of model representations that affect model-to-brain alignment. For example, Kauf et al (2024) performed a series of experiments where model representations were obtained for different perturbations of a linguistic stimulus (e.g., scrambling the word order or dropping/replacing some of the words) and then related to neural representations of an intact stimulus in order to see which perturbations affect model representations negatively. They found that word-level and compositional semantic information appears to be more important than information related to the syntactic structure in the model-to-brain alignment.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into what aspect of the captions produced high alignment between the language models and the brain/behavior, we performed selective perturbations to the captions as in [27,52], but instead of deletion, we performed masking to keep the overall syntactic structure of the sentence intact. We used the spaCy [53] package and the en_core_web_sm model in particular to identify the parts of speech for masking.…”
Section: Caption Perturbation Experimentsmentioning
confidence: 99%